2001
DOI: 10.1007/bf03185218
|View full text |Cite
|
Sign up to set email alerts
|

Force modeling and machining characteristics of the intermittent grinding wheels

Abstract: In the surface grinding operations, the grinding fluid cannot be supplied sufficiently in the cutting zone. Temperature generated in the cutting zone increases rapidly and causes thermal damage such as burning on the surface of a workpiece. To reduce thermal damage, the intermittent grinding wheels, which have an excellent cooling effect, have been applied. This paper describes machining characteristics by using intermittent grinding wheels. The grinding force of the intermittent wheels has been simulated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…For an intermittent dress grinding process [11], the interaction between the grinding wheel and the workpiece is cyclic. In this case the local heat transfer coefficient bðt; xÞ and the surface heat flux dðt; xÞ were given in [3] in terms of the Heaviside step function H [12] bðt; xÞ ¼ aH ðÀxÞ þ aH ðx À dÞ þ a s H ðd À xÞH ðxÞf s ðtÞ þaH ðd À xÞH ðxÞf e ðtÞ;…”
Section: Numerical Methods Formulaementioning
confidence: 99%
“…For an intermittent dress grinding process [11], the interaction between the grinding wheel and the workpiece is cyclic. In this case the local heat transfer coefficient bðt; xÞ and the surface heat flux dðt; xÞ were given in [3] in terms of the Heaviside step function H [12] bðt; xÞ ¼ aH ðÀxÞ þ aH ðx À dÞ þ a s H ðd À xÞH ðxÞf s ðtÞ þaH ðd À xÞH ðxÞf e ðtÞ;…”
Section: Numerical Methods Formulaementioning
confidence: 99%
“…So, the proper use of coolant and its application are indispensable to cool the workpiece and avoid thermal damages [14]. Nevertheless, Kwak and Ha [15] demonstrated that grinding by interrupted cutting (grinding wheel with grooves) is a promising method to decrease workpiece thermal damages due to the excellent cooling effect of the process. According to Pérez et al [16], the explanation is based on the grooves, since they provide direct and enough amount of cutting fluid in the cutting zone.…”
Section: Grinding Process Cooling In Interrupted Cuttingmentioning
confidence: 99%
“…19 With the results of the experiments with conventional and intermittent wheels, it was proven that the intermittent wheel appeared to be superior in various aspects such as the grinding force, the temperature and the geometric error, showing little deterioration of the surface roughness. Tawakoli and Azarhoushang 20 investigated the feasibility of intermittent grinding with a segmented wheel, using two ceramic-matrix composite materials.…”
Section: Introductionmentioning
confidence: 96%